System management and monitoring : temporal evaluation of freeway management systems - Coifman, Benjamin; Redmill, Keith; Merry, Carolyn (Midwest Regional University Transportation Center, 2005)
Virtually every major metropolitan area in the US has a traffic monitoring system to help increase traffic throughput, decrease the number of accidents, decrease the time required to clear incidents that disrupt flow, and provide travelers information. Almost all of these systems are myopic, focusing strictly on current conditions. Yet the data collected by the sensors can provide considerable information when viewed over time. The goal of this study is to investigate and demonstrate several applications that employ traffic monitoring system data over time to show the added benefit of the given system. Many of these tools have been demonstrated in real time using data from the Columbus Metropolitan Freeway Management System (CMFMS), the intelligent freeway management system in the greater Columbus, Ohio area.
33 p.
Keywords: Freeway management systems; Traffic measurement; Traffic surveillance